Statistical-Experimental Investigation of the Effect of Focal Length and Displacement on Laser Drilling of Hastelloy-X Superalloy Sheet using Single Pulse Fiber Laser - Mostafa Ghadimi Dafrazi; Reza Shoja Razavi; Masood Barkat; Ali Khoram; Mohammad Erfanmanesh (Journal of Advanced Materials in Engineering)
Introduction and Objectives: In this research, the laser drilling process was carried out by a single pulse method and the effect of displacement and focal length parameters on the geometry of the hole (Inlet diameter, Outlet diameter, Taper, and Entrance circularity error) was studied.Materials and Methods: In this study, statistical-experimental modeling was done using a full factorial experiment design with two factors of displacement and focal length in ten and seven levels on Hastelloy-X superalloy, respectively. Also, four cases of inlet and outlet hole diameter, cone angle, and circularity of the inlet diameter were considered as responses to the design of the experiment.Results: The results showed that the diameter of the inlet and outlet holes increased with the increase of displacement and positive changes in the focal length. Also, the variation of the hole diameter was quite acceptable from 183 μm to 1768 μm with the single pulse method on the Hastelloy-X sheet with a thickness of 1 mm.Conclusion: The optimized results of the answers revealed that the maximum value of the hole inlet diameter was 997.848 μm, the maximum hole outlet diameter was 771.341 μm, the taper was 6.492 degrees, and finally the entrance circularity error was 0.0167.